Utilization of e-book 3-dimensions information systems based on google analytics - Kamaludin (Mr.) Kamaludin Kamaludin; Dwiyanto Wahyu Ari Nugroho; Ridwan Suhud; Rahmahwati . (UPT Perpustakaan UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
The use of information and communication technology has become a necessity for people to search for information and information published in 3-dimensional e-book media, which has been widely used in information retrieval. This paper aims to determine the use of 3-dimensional e-Books produced by the Directorate of Repository, Multimedia, and Scientific Publishing-National Information Research Agency. The method used in this research is the Google Analytics method, an application that provides information on the results of data collection (data mining) using the web using page tag techniques. With Google Analytics, the collected data related to acquisition and user behavior on the web can be analyzed to be used as a goal, reference, and reliable data. The results showed that there were 304 (three hundred and four) titles of 3-dimensional E-Books produced, which were grouped into 12 categories. Users of 3-dimensional E-Books are spread across 12 (twelve) countries. The two countries that use the most are Indonesia, with 2,718 users (94.05%), followed by America with 72 users (2.49%). Meanwhile, the two most widely used 3-dimensional e-book categories were the tourism category with 625 (31.2%) and animal husbandry and agriculture 421 (21.0%). Considering that users of this 3-dimensional e-book are scattered in various countries, it is recommended that the production of this 3-dimensional e-book can be continued.